TP1.2.7The stuck colonoscope. (28th October 2021) - Sebastian, B; Mirshekar-Syahkal, B; Athisayaraj, T; Ward, N
Abstract: Background: With the increased awareness and push for earlier diagnosis of colorectal cancer, the number of patients undergoing colonoscopy is increasing. Being a common condition, a number of these patients will have herniae. We describe a rare complication during a Sigmoidoscopy in a patient with an Inguinal hernia. The case: A 75-year-old man was booked for a flexible sigmoidoscopy for rectal bleeding. The scope was successfully inserted to the Splenic flexure. During withdrawal, the scope stopped moving. It was still possible to advance the scope, but not to withdraw. The patient confirmed the presence of a left inguinal hernia. Physical examination and the position on magnetic scope imager confirmed the loop in the hernia. Various manoeuvres to withdraw the scope were unsuccessful. A colleague was called for a second opinion. We came up with a plan to maintain a 'long loop' position in the hernia, by holding the scope through the scrotum and allowing it to slide on withdrawal. This was successful and the patient was discharged. Discussion: Incarceration of the scope in the hernia occurs when the hernial defect permits entry and exit of the scope, leaving a loop in the hernia, in a long loop position. During withdrawal, the configuration changes to a short loop, crowding the hernial defect, preventing the scope from sliding. On searching literature, we found that this technique has been described by Koltun et al and is known as the "Pulley" technique. We suggest that colonoscopists are familiar with this technique.